The health and economic impact of switching vaccines in universal varicella vaccination programs using a dynamic transmission model: An Israel case study - Stephanie A. Kujawski; Colleen Burgess; Oren Agi; Zohar Attias-Geva; Matthew Pillsbury; David Greenberg; Goran Bencina; Manjiri Pawaskar (Human Vaccines & Immunotherapeutics, 2022)
Currently available health economic models for varicella infection are designed to inform the cost-effectiveness of universal varicella vaccination (UVV) compared with no vaccination. However, in countries with an existing UVV program, these models cannot be used to evaluate whether to continue with the current varicella vaccine or to switch to an alternative vaccine. We developed a dynamic transmission model that incorporates the historical vaccination program to project the health and economic impact of changing vaccination strategies. We applied the model to Israel, which initiated UVV in 2008 with a quadrivalent vaccine, MMRV-GSK, and switched to MMRV-MSD in 2016. The model was calibrated to pre-vaccination incidence data before projecting the impact of the historical and future alternative vaccination strategies on the clinical burden of varicella. Total costs and QALYs lost due to varicella infections were projected to compare continuing with MMRV-MSD versus switching to MMRV-GSK in 2022. Over a 50-year time horizon, continuing with MMRV-MSD reduced varicella incidence further by 64%, reaching 35 cases per 100,000 population by 2072, versus a 136% increase in incidence with MMRV-GSK. Continuing with MMRV-MSD reduced cumulative hospitalization and outpatient cases by 48% and 58% (vs. increase of 137% and 91% with MMRV-GSK), respectively. Continuing with MMRV-MSD resulted in 139 fewer QALYs lost with total cost savings of 3% compared with switching to MMRV-GSK, from the societal perspective. In Israel, maintaining the UVV strategy with MMRV-MSD versus switching to MMRV-GSK is projected to further reduce the burden of varicella and cost less from the societal perspective.